Indications and surgical management for movement disorders - Alhayen, Basem Ismail; Abdel-Bari, Sameh Hamdi Hassan; Mohammad, Mohammad Edrees; Ayoub, Basim Mohamed; Ali, Ramy Amin Kamel (South Eastern European Journal of Public Health, 2025)
Background: Movement disorders encompass a heterogeneous group of neurological conditions affecting motor control. These disorders are broadly classified into hypokinetic (e.g., Parkinson’s disease [PD]) and hyperkinetic (e.g., dystonia, essential tremor). While pharmacological treatment remains the mainstay, stereotactic neurosurgical procedures, including lesioning techniques such as thalamotomy and pallidotomy, offer an effective alternative for medically refractory cases. Despite the high success rate of deep brain stimulation (DBS), financial constraints in developing countries necessitate more cost-effective approaches like lesioning procedures. Aim: This study aimed to evaluate the outcomes of lesioning procedures in patients with movement disorders, specifically Parkinson’s disease, dystonia, and essential tremor. The study also sought to establish a standardized protocol for surgical management, considering economic constraints, and to enhance collaboration between neurology and neurosurgery departments for optimal patient care. Patients and Methods: A prospective clinical study was conducted at Cairo University Hospitals from May 2022 to February 2023, enrolling 21 patients diagnosed with movement disorders. Patients underwent stereotactic lesioning procedures, including thalamotomy and pallidotomy, based on clinical symptomatology. Preoperative and postoperative assessments utilized standardized scoring systems such as the Unified Parkinson’s Disease Rating Scale (UPDRS), TETRAS (essential tremor rating scale), and the Unified Dystonia Rating Scale (UDRS). Statistical analysis was performed using SPSS version 26, with significance set at P < 0.05. Results: Among the 21 patients, 16 had Parkinson’s disease, 3 had essential tremors, and 2 had dystonia. Postoperative assessments showed significant improvement across all groups. In Parkinson’s disease patients, UPDRS III scores improved by 46.3% in the off-medication state and 57.7% in the on-medication state (P < 0.001). Tremors decreased by 60% in the off state and 75% in the on state. Essential tremor patients exhibited a 41.5% improvement in TETRAS scores (P = 0.011), while dystonia patients showed a 41.5% improvement in UDRS scores (P = 0.033). Mild dysarthria was reported in 18.75% of Parkinson’s patients, with one case of postoperative subdural hematoma. Conclusion: We conclude that lesioning procedure should be revisited globally using the modern techniques of targeting and controlled thermal lesion protocols guided by capsular somatotopy and intraoperative EMG monitoring, that will improve the outcome dramatically